Back Cover: Synthesis of Tetrazino‐tetrazine 1, 3, 6, 8‐Tetraoxide (TTTO) (Angew. Chem. Int. Ed. 38/2016). Issue 38 (3rd August 2016) - Klenov, Michael S.; Guskov, Alexey A.; Anikin, Oleg V.; Churakov, Aleksandr M.; Strelenko, Yurii A.; Fedyanin, Ivan V.; Lyssenko, Konstantin A.; Tartakovsky, Vladimir A.
Abstract : A high‐energy molecule can be thermally stable if its structure shows alternating charges. In their Communication onpage 11472 ff., A. M. Churakov et al. report the synthesis of a new nitrogen system 1, 2, 3, 4‐tetrazino[5, 6‐ e ]‐1, 2, 3, 4‐tetrazine‐1, 3, 6, 8‐tetraoxide. The synthetic strategy was based on the sequential closure of two 1, 2, 3, 4‐tetrazine 1, 3‐dioxide rings by the generation of oxodiazonium ions and their intramolecular coupling with tert ‐butyl‐ NNO ‐azoxy groups.